The Tonsil Lymphocyte Landscape in Pediatric Tonsil Hyperplasia and Obstructive Sleep Apnea - Carrasco, Anna; Sjölander, Isabella; Van Acker, Aline; Dernstedt, Andy; Fehrm, Johan; Forsell, Mattias; Friberg, Danielle; Mjösberg, Jenny; Rao, Anna (Frontiers in Immunology, 2021)
Tonsil hyperplasia is the most common cause of pediatric obstructive sleep apnea (OSA). Despite the growing knowledge in tissue immunology of tonsils, the immunopathology driving tonsil hyperplasia and OSA remains unknown. Here we used multi-parametric flow cytometry to analyze the composition and phenotype of tonsillar innate lymphoid cells (ILCs), T cells, and B cells from pediatric patients with OSA, who had previous polysomnography. Unbiased clustering analysis was used to delineate and compare lymphocyte heterogeneity between two patient groups: children with small tonsils and moderate OSA (n = 6) or large tonsils and very severe OSA (n = 13). We detected disturbed ILC and B cell proportions in patients with large tonsils, characterized by an increase in the frequency of naïve CD27-CD21hi B cells and a relative reduction of ILCs. The enrichment of naïve B cells was not commensurate with elevated Ki67 expression, suggesting defective differentiation and/or migration rather than cellular proliferation to be the causative mechanism. Finally, yet importantly, we provide the flow cytometry data to be used as a resource for additional translational studies aimed at investigating the immunological mechanisms of pediatric tonsil hyperplasia and OSA.